Functionally Important Amino Acids in the Arabidopsis Thylakoid Phosphate Transporter: Homology Modeling and Site-Directed Mutagenesis - Ruiz-Pavón, Lorena; Karlsson, Patrik M; Carlsson, Jonas; Samyn, Dieter; Persson, Bengt; Persson, Bengt L; Spetea, Cornelia (Biochemistry (Easton), 2010)
The anion transporter 1 (ANTR1) from Arabidopsis thaliana, homologous to the mammalian members of the solute carrier 17 (SLC17) family, is located in the chloroplast thylakoid membrane. When expressed heterologously in Escherichia coli, ANTR1 mediates a Na+-dependent active transport of inorganic phosphate (Pi). The aim of this study was to identify amino acid residues involved in Pi binding and translocation by ANTR1 and in the Na+ dependence of its activity. A three-dimensional structural model of ANTR1 was constructed using the crystal structure of glycerol 3-phosphate/phosphate antiporter from E. coli as a template. Based on this model and multiple sequence alignments, five highly conserved residues in plant ANTRs and mammalian SLC17 homologues have been selected for site-directed mutagenesis, namely, Arg-120, Ser-124, and Arg-201 inside the putative translocation pathway and Arg-228 and Asp-382 exposed at the cytoplasmic surface of the protein. The activities of the wild-type and mutant proteins have been analyzed using expression in E. coli and radioactive Pi transport assays and compared with bacterial cells carrying an empty plasmid. The results from Pi- and Na+-dependent kinetics indicate the following: (i) Arg-120 and Arg-201 may be important for binding and translocation of the substrate; (ii) Ser-124 may function as a transient binding site for Na+ ions in close proximity to the periplasmic side; (iii) Arg-228 and Asp-382 may participate in interactions associated with protein conformational changes required for full transport activity. Functional characterization of ANTR1 should provide useful insights into the function of other plant and mammalian SLC17 homologous transporters.